Solving the Policy Implementation Problem - Garn, Gregg A. (Education Policy Analysis Archives, 1999)
When Republican legislators in Arizona failed to approve educational vouchers in four consecutive legislative sessions, a charter school program was approved as a compromise. The charter school policy was written during a special summer session and within three years, over 30,000 students were enrolled in 260 charter schools across the state. Republican policy makers, who failed to enact voucher legislation, proclaimed the charter school program to be an overwhelming success and protected it from amendments by Democrats and potential actions of bureaucrats that could have altered the policy intent. Research on the implementation of policy indicates that state and local implementors frequently undermine or alter legislative intentions. However, when Arizona policy makers approved the charter school policy, they overcame this persistent implementation phenomenon and, in fact, succeeded in preserving the legislative intentions in the working program. This policy study analyzes how they were able to achieve this elusive result. Key policy makers attended to four significant features of policy implementation in creating the charter school policy: communication, financial resources, implementor attitudes, and bureaucratic structure. Manipulating these key variables allowed policy makers to reduce implementation slippage.